Consumer acceptance of biofortified foods - Birol, Ekin; Oparinde, Adewale; Banerji, Abhijit; Meenakshi, Jonnalagadda V.; Chowdhury, Shyamal; Tomlins, Keith; De Groote, Hugo; Manyong, Victor M.; Perez, Salomon (International Food Policy Research Institute, 2014)
The economic feasibility of maize flour and maize meal fortification in Kenya, Uganda, and Zambia is assessed using information about the maize milling industry, households’ purchases and consumption levels of maize flour, and the incremental cost and estimated price impacts of fortification. Premix costs comprise the overwhelming share of incremental fortification costs and vary by 50% in Kenya and by more than 100% across the three countries. The estimated incremental cost of maize flour fortification per metric ton varies from $3.19 in Zambia to $4.41 in Uganda. Assuming all incremental costs are passed onto the consumer, fortification in Zambia would result in at most a 0.9% increase in the price of maize flour, and would increase annual outlays of the average maize flour–consuming household by 0.2%. The increases for Kenyans and Ugandans would be even less. Although the coverage of maize flour fortification is not likely to be as high as some advocates have predicted, fortification is economically feasible, and would reduce deficiencies of multiple micronutrients, which are significant public health problems in each of these countries.